Meningkatkan Kemampuan Presentasi karya Ilmiah yang Efektif bagi siswa KIR BERSINAR SMA Negeri 1 Kajen Kabupaten Pekalongan - Afifa Nur Hasanah; Silva Asti Ananta; Lutfiyanti Lutfiyanti; Mia Aulia Rahmah; Nafal Fikri (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
This community service activity aims to improve the scientific presentation skills of students from KIR BERSINAR at SMA Negeri 1 Kajen through an interactive socialization program on effective and engaging scientific paper presentation techniques. The implementation methods included delivering materials using PowerPoint slides, conducting interactive quizzes via the Quiziz application, and holding discussions followed by drawing conclusions. The activity was attended by 15 students and carried out in three stages: preparation, implementation, and closing. The results showed a significant improvement in students’ understanding of scientific presentation techniques, including structuring material, using communicative language, and enhancing public speaking skills. The participants demonstrated high enthusiasm, actively engaged in discussions, and responded well to questions. Quiz results indicated that most students were able to comprehend and apply the material presented. Furthermore, the activity fostered students’ confidence in expressing their ideas and opinions orally. Overall, this community service activity made a positive contribution to developing students’ scientific communication skills and strengthening the academic culture within the school environment.